Optimization Of Financial Inclusion Through Sharia Banking Redistributive Instruments - Novia Nengsih (Universitas Islam Negeri (UIN) Walisongo Semarang, 2020)
Purpose - This study aims to analyze the optimization of financial inclusion using Islamic banking redistributive instruments.Method - This study aims to analyze the optimization of financial inclusion using Islamic banking redistributive instruments.Result - The main finding of this research is that Islamic banking can optimize financial inclusion using the redistributive instruments of syari'ah banking, namely zakat, Qardul Hasan, and other merit funds. This is indicated by the growth of zakat funds, benevolence funds, and increased qardul hasan financing.Implication - This research can be used as a reference to determine the optimization of financial inclusion by Islamic banking using the redistributive instrument of zakat, qardhul hasan, and other merit funds.Originality - This study analyzes the optimization of financial inclusion through the redistributive instrument of Islamic banking with qualitative and quantitative approaches.